2013
DOI: 10.1371/journal.pone.0056836
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Receptor I (IGF-IR) and Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2) Are Expressed on the Circulating Epithelial Tumor Cells of Breast Cancer Patients

Abstract: BackgroundCirculating epithelial tumor cell (CETC) analysis is a promising diagnostic field for estimating the risk for metastatic relapse and progression in patients with malignant disease. CETCs characterization can be used as a liquid biopsy for prognostic and predictive purposes in breast and other cancers. IGF-IR and VEGFR-2 play an important role in tumor growth and the progression of cancer disease. The purpose of the current study was therefore to investigate their expression on CETCs.MethodsCETCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
0
12
0
3
Order By: Relevance
“…Insulin-like growth factor-1 receptor-expressing CTCs were detected in the majority of patients with early or metastatic breast cancer. Similarly, de Bono et al (2007) also showed that IGF1R is frequently expressed in CTCs of patients with metastatic tumors, whereas Pizon et al (2013) reported that 84% of patients with breast cancer had IGF1R-expressing CTCs. Interestingly, here we report that IGF1R immunostaining is more frequently observed among CTCs in early compared to metastatic disease.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Insulin-like growth factor-1 receptor-expressing CTCs were detected in the majority of patients with early or metastatic breast cancer. Similarly, de Bono et al (2007) also showed that IGF1R is frequently expressed in CTCs of patients with metastatic tumors, whereas Pizon et al (2013) reported that 84% of patients with breast cancer had IGF1R-expressing CTCs. Interestingly, here we report that IGF1R immunostaining is more frequently observed among CTCs in early compared to metastatic disease.…”
Section: Discussionmentioning
confidence: 94%
“…() also showed that IGF1R is frequently expressed in CTCs of patients with metastatic tumors, whereas Pizon et al . () reported that 84% of patients with breast cancer had IGF1R‐expressing CTCs. Interestingly, here we report that IGF1R immunostaining is more frequently observed among CTCs in early compared to metastatic disease.…”
Section: Discussionmentioning
confidence: 98%
“…VEGFRs are the most important molecular targets for tumor therapy. VEGFR‐1 and VEGFR‐2 are overexpressed not only in endothelial cells, but also in many kinds of non‐endothelial tumor cells (Bairey et al , ; Spannuth et al , ; Pizon et al , ). It has been reported that VEGFRs overexpression are detected in most clinic human OSCC specimens (Ariotti et al , ; Pianka et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The Pathology Atlas database indicates that VEGFR2 protein can be detected by immunohistochemical staining with verified Abs in cancer cells of 10%‐40% of surgical tumor sections, including urothelial, prostate, head and neck, cervical, and skin cancer . Interestingly, circulating tumor cells in the blood of breast cancer and small‐cell lung cancer patients were also found to express VEGFR2, and such expression is associated with tumor metastasis and poor prognosis . Therefore, blocking VEGFR2‐mediated signaling in both tumor endothelial and malignant cells is considered to be a promising strategy for new cancer treatments …”
Section: Introductionmentioning
confidence: 99%